Mega-crime, legitimacy, legality, and obedience - Leman-Langlois, Stéphane (Criminologie)

(untitled) (Les Presses de l’Université de Montréal, 2022)
This paper reviews several current theories in criminology and evaluates their ability to account for “mega-crimes” (acts that lead to large-scale loss of human life and are widely acknowledged at the international level to be criminal ). The exercise shows that criminology is incapable of explaining mega-crimes. It is not that such acts are outside its defined field of study – they, like common crimes, are voluntary, organized actions that cause damage to victims and lead to interaction with various judicial systems – but because of its narrow and persistent focus on purely individual conduct.